1985
DOI: 10.1007/bf00555260
|View full text |Cite
|
Sign up to set email alerts
|

The plastic deformation of ultra-high molecular weight polyethylene

Abstract: Gel-spun filaments of different initial morphologies have been subjected to controlled drawing at elevated temperatures. The drawn samples have been examined by highresolution scanning electron microscopy. The deformation mechanism at temperatures up to 120 ~ C is very similar to crazing, especially in the case of unoriented gel-spun filaments. Filaments exhibiting a shish-kebab morphology offer the opportunity of examining the deformation of elementary fibrils in a quantitative way. The transformation of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…While some microfibrils are measured as small as 16 nm and greater than 90 nm, over 70 percent of the fibrils measured are between 20 and 40 nm. These dimensions, consistent with similar measurements via SEM in the literature [43], correlate quite well with the crystallite dimensions calculated from WAXD measurements. This suggests that the majority of microfibrils are arrays of single crystals linked in series.…”
Section: Surface Morphology Of Highly Drawn S130supporting
confidence: 87%
“…While some microfibrils are measured as small as 16 nm and greater than 90 nm, over 70 percent of the fibrils measured are between 20 and 40 nm. These dimensions, consistent with similar measurements via SEM in the literature [43], correlate quite well with the crystallite dimensions calculated from WAXD measurements. This suggests that the majority of microfibrils are arrays of single crystals linked in series.…”
Section: Surface Morphology Of Highly Drawn S130supporting
confidence: 87%
“…melt-spinning or fibres prepared from semi-dilute polymer solutions) and the process variables, as extensively described in the literature [27,29,[30][31][32][33][34][35]. During cold-drawing the lamellar structures are transformed into fibrillar structures by rotation/translation of (parts of) lamellae and/or by local melting of the lamellae due to local high stress concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Hot-drawing was possible up to a maximum hot-draw ratio of 80 and this resulted in a fiber with a tensile strength of 3.55 GPa. SEM and SAXS studies of the hot-drawing process of these gel-spun fibers revealed that for high hot-draw ratios the lamellar structure was transformed into a fibrillar structure [32,33]. Hot-drawing to lowdraw ratios resulted in a decrease of the crystallinity and a shift of the peak melting temperature Tm to somewhat lower temperatures due to a recrystallization of the lamellar material into less perfect crystals, due to fast cooling of the thin hot-drawn fibers.…”
Section: Melting Behavior Of Extracted Gel-~pun Polyethylene Fibersmentioning
confidence: 98%